Perfil fitoquímico, atividade antimicrobiana e potencial antioxidante de Cyperaceae Juss. - Bezerra, José Jailson Lima (2019)
The Cyperaceae family is characterized by an herbaceous habit of life, sessile leaves and fruits of the aquarium type, being widely distributed in several parts of the world. In pharmacological and phytochemical aspects, the species of this family present bioactive compounds that confer a range of biologically proven scientific activities. In this way, the present research was carried out with the objective of characterizing the phytochemical profile and to evaluate the antimicrobial and antioxidant activities of the family Cyperaceae, through studies using the aerial and subterranean parts of the species Cyperus articulatus L.; Cyperus iria L.; Kyllinga odorata Vahl; Oxycaryum cubensis Poepp. & Kunth e Rhynchospora nervosa Boeck. The vegetal material was collected in specific areas of the state of Alagoas and pulverized in knives mills to obtain the powder. Subsequently, hydroalcoholic extracts (50%) were prepared from the aerial and subterranean parts of the five species collected. A liquid-liquid partitioning was used to obtain phases of ethyl acetate and chloroform. To analyze the chemical constitution of the crude extracts, the following tests were performed: a) phytochemical screening; b) identification of chemical compounds by high performance liquid chromatography (HPLC-DAD); c) quantification of total flavonoid content by complexation with AlCl3; d) quantification of the total phenol content using the FolinCiocalteu reagent. The evaluation of the antioxidant activity in vitro was performed against the radical DPPH (2,2-difenil-1-picril hidrazila). In vitro antimicrobial assays were performed in triplicates using the serial microdilution technique in order to evaluate the Minimum Inhibitotia Concentration (MIC) of the ethyl acetate and chloroform phases against Staphylococcus aureus (ATCC 27664), Pseudomonas aeruginosa (ATCC 25619) and Candida albicans (ATCC 36802). The results of phytochemical screening indicated the presence of several phenolic compounds in the hydroalcoholic extracts of C. articulatus, C. iria, K. odorata, O. cubensis and R. nervosa. By means of the HPLC-DAD technique using the ethyl acetate and chloroform phases of the five species studied, substances of great pharmacological importance were identified, such as: apigenin, catechin, quercetin, luteolin and chrysin. In the tests concerning quantification of flanoid and total phenol content, the hydroalcoholic extracts of the aerial parts of these species showed higher levels of these substances when compared to the subterranean parts, therefore, they expressed better results in the evaluation of the antioxidant activity in vitro by the DPPH method. In relation to the antimicrobial activity, it was verified that chloroform phases had a greater inhibitory activity when tested against the pathogenic microorganisms. The subterranean parts of O. cubensis inhibited the growth of C. albicans, S. aureus and P. aeruginosa at concentrations of 15,6; 31,2 and 62 μg/mL, respectively. The chloroform phase of C. iria also have shown an excellent result, requiring a concentration of only 31,2 μg/mL to inhibit the growth of C. albicans and S. aureus. Therefore, these species can be sources of bioactive compounds effective against fungi and bacteria.